Current aspects of targeting cellular senescence for the therapy of neurodegenerative diseases - Jaganathan, Ravindran; Iyaswamy, Ashok; Krishnamoorthi, Senthilkumar; Thakur, Abhimanyu; Durairajan, Siva Sundara Kumar; Yang, Chuanbin; Wankhar, Dapkupar (Frontiers in Aging Neuroscience, 2025)
IntroductionAging is a normal process causing deterioration in normal brain function and is inevitable. The aging process is described by the buildup of senescent cells and a decline in the ability to maintain essential homeostatic functions. Cellular aging represents a critical process where cells undergo cell cycle arrest in response to stress and neuronal damage. Many neurodegenerative disorders are closely linked to cellular senescence caused by oxidative stress, ROS generation, and DNA damage. Therefore, targeting cellular senescence is essential for the therapy of neurodegenerative disorders.MethodsThis review outlines the understanding of cellular senescence, its role in the aging process, signaling pathways, autophagy, lysosomal biogenesis, and its contribution to various neurodegenerative disorders.ResultsThe findings highlight the relationship between cellular senescence and neurodegenerative disorders, emphasizing its pathological role. Current evidence indicates that senolytic drugs, notably phytochemicals such as dasatinib, quercetin, and fisetin, could serve as therapeutic approaches to target senescent cells and improve outcomes in neurodegenerative illnesses.DiscussionThis review conclusively addresses the possibility of senolytic interventions for the treatment of neurodegenerative diseases. It will encourage researchers to identify novel compounds or phytochemicals that could be used as senolytic drugs for treating numerous neurodegenerative disorders.